Location and coupling interval of an ectopic excitation determine the initiation of atrial fibrillation from the pulmonary veins. (25th January 2022) - Kawai, Shunsuke; Mukai, Yasushi; Inoue, Shujiro; Yakabe, Daisuke; Nagaoka, Kazuhiro; Sakamoto, Kazuo; Takase, Susumu; Chishaki, Akiko; Tsutsui, Hiroyuki
Abstract: Introduction: Ectopic beats originating from the pulmonary vein (PV) trigger atrial fibrillation (AF). The purpose of this study was to clarify the electrophysiological determinant of AF initiation from the PVs. Methods: Pacing studies were performed with a single extra stimulus mimicking an ectopic beat in the left superior PVs (LSPVs) in 62 patients undergoing AF ablation. Inducibility of AF, effective refractory period (ERP), and conduction properties within the PVs were analyzed. Results: A single extra stimulus in LSPV induced AF in 20 patients (32% of all patients) at the mean coupling interval (CI) of 172 ms. A CI‐dependent anisotropic conduction at the AF onset was visualized in a three‐dimensional mapping. Onset of AF was site‐specific with reproducibility in each individual. Mean ERP in LSPV in the AF‐inducible group was shorter than that in the AF‐noninducible group (182 ± 55 vs. 254 ± 51 ms, p < .0001). LSPV ERP dispersion was greater in the AF‐inducible group than in the AF‐noninducible group (45 ± 28 vs. 27 ± 19 ms, p < .01). Circumferential intra‐PV conduction time (IPVCT) exhibited decremental properties in response to shortening of CI and the prolongation of IPVCT in the AF‐inducible site was greater than that in the AF‐noninducible site ( p < .05) in each individual. Conclusions: Location and CI of an ectopic excitation ultimately determine the initiation of AF from the PVs. ERP dispersion and circumferential conduction delay may lead to anisotropic conduction and reentry within the PVs that initiate AF.